2008
DOI: 10.2174/1875318300801010028
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of n-6 Polyunsaturated Fatty Acid on Blood Levels of Malondialdehyde-Deoxyguanosine Adducts in Human Subjects

Abstract: Abstract:The role of n-6 polyunsaturated fats upon the formation of the mutagenic DNA adduct malondialdehydedeoxyguanosine (M 1 dG) in blood was investigated in male volunteers (n = 13) who consumed diets high in saturated and polyunsaturated fats, and polyunsaturated fat plus a-tocopherol supplemention (400 IU per day). On day 14 there was a significant difference in adduct levels between diets with saturated fats giving higher levels than polyunsaturated fats but this effect had disappeared by day 20 indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The analysis of blood samples is particularly relevant for biomonitoring studies if they are to be as non-invasive as possible. The results for M 1 dG in colorectal mucosa samples from the EPIC study had been previously reported and a weak correlation was found with dietary saturated fat (18) which was corroborated in an intervention study using blood samples (22). The corresponding EPIC blood samples have now been analysed and the results are reported in this paper.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…The analysis of blood samples is particularly relevant for biomonitoring studies if they are to be as non-invasive as possible. The results for M 1 dG in colorectal mucosa samples from the EPIC study had been previously reported and a weak correlation was found with dietary saturated fat (18) which was corroborated in an intervention study using blood samples (22). The corresponding EPIC blood samples have now been analysed and the results are reported in this paper.…”
Section: Introductionsupporting
confidence: 76%
“…However, an intervention study had demonstrated the importance of taking samples at appropriate time points (22).…”
Section: O 6 Cmdg Adducts In Blood Samples From a Processed Meat Studymentioning
confidence: 99%
“…M 1 dG adducts have been positively associated with smoking, alcohol . and diets high in saturated fatty acids . However, there is still ambiguity between studies with associations not always being found.…”
mentioning
confidence: 99%
“…It is known to be mutagenic in bacterial [3] and mammalian cells, [4] and enhances DNA damage caused by some chemicals. [5] Lifestyle factors such as smoking, [6][7][8][9] high fat diets [2,[10][11][12] and alcohol [1] have been associated with increased MDA levels and there is a vast body of evidence that links these to many types of cancer including, but not limited to, lung, breast and colorectal cancers. [13] Thus, MDA is widely used as a marker of oxidative stress and potential disease risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation